Critical component wear in heavy duty engines - Lakshminarayanan, P. A.; Nayak, Nagaraj S.; Wiley InterScience (Online service) (Hoboken, N.J. : Wiley, 2011)
"Shows engineers how to prevent wear and dramatically increase the lifespan of key componentsThe critical parts of a heavy duty engine are designed for infinite life without mechanical fatigue failure. Yet the life of an engine is in reality determined by wear of the critical parts. Even if an engine is reconditioned at the end of normal wear life, abnormal wear takes place either due to special working conditions or increased loading. Understanding abnormal and normal wear enables the engineer to control the external conditions leading to premature wear, or to design the critical parts that have longer life and hence lower costs. The literature on wear phenomenon related to engines is scattered in numerous periodicals and books. For the first time, the tribology aspects of different critical engine components are written in one book. Lakshminarayanan covers tribology of critical components, namely, the liner, piston, rings, valve, valve train and bearings with methods to identify and quantify wear. Presents real world case studies with suitable mathematical models for earth movers, power generation, and sea going vessels Includes material from researchers at Chevron (USA), Tekniker (Spain), IP Rings (India), Kirloskar Oil Engines Ltd (India) Wear simulations and calculations included in the appendices Instructor presentations slides with book figures available from the companion site "--
"While these have been well addressed by the engineering community the solutions are scattered in different journals and books. This book brings the solutions together into one volume"--
Front Matter -- Overture. Wear in the Heavy Duty Engine -- Engine Size and Life -- Valve Train Components. Inlet Valve Seat Wear in High bmep Diesel Engines -- Wear of the Cam Follower and Rocker Toe -- Liner, Piston and Piston Rings. Liner Wear: Wear of Roughness Peaks in Sparse Contact -- Generalized Boundary Conditions for Designing Diesel Pistons -- Bore Polishing Wear in Diesel Engine Cylinders -- Abrasive Wear of Piston Grooves in Highly Loaded Diesel Engines -- Abrasive Wear of Liners and Piston Rings -- Corrosive Wear -- Tribological Tests to Simulate Wear on Piston Rings -- Engine Bearings. Friction and Wear in Engine Bearings -- Lubricating Oils for Modern Engines. Heavy Duty Diesel Engine Oils, Emission Strategies and their Effect on Engine Oils -- Fuel Injection Equipment. Wear of Fuel Injection Equipment -- Heavy Fuel Engines. Wear with Heavy Fuel Oil Operation -- Filters. Air and Oil Filtration and Its Impact on Oil Life and Engine Wear Life -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Internal combustion engines; Machine parts -- Failures; Mechanical wear; TECHNOLOGY & ENGINEERING -- Machinery; Internal combustion engines; Machine parts -- Failures; Mechanical wear; Electronic books